Reflections on the professional identity of supervising nurses in hospital environments (Brazilian Journal of Health Research, 2021)
Introduction: Identity is not limited to choosing a trade or acquiring a diploma. The nurse’s work is marked by the dichotomy between management and care activities, which affect technical and legal attributions and responsibilities. Objective:Identifying the working processes carried out by nurses’ supervisors in hospital environments and their interface with professional identity. Methods: Descriptive exploratory study with qualitative approach carried out with nine nurses who worked in a hospital in Bahia State’s countryside, in 2018. Interview guided by semi-structured instrument was the herein adopted technique. Hermeneutic dialectic, based on Sanna’s theoretical framework, was used for data analysis. Results: Categories resulting from the analysis were named based on the working process adopted by supervising nurses (managing, assisting, teaching, politically participating and researching). The study has shown that the establishment of working routine processes is pointed out by the investigated supervisors as necessary for the establishment of managerial skills. Determining factors of supervising nurses’ professional identity in hospital environments are associated with the dimensions of their working process. Conclusion: The professional identity of these nurses is associated with the working processes performed by them (or not) and with elements enabling their identity as nurses, a fact that influences the way they act in the supervision of Nursing teams and health services.
Keywords: Social Identification; Nurses; Nursing supervision; Hospital Management